Perbandingan Tingkat Keparahan Infeksi Sekunder Virus Dengue pada Keempat Serotipe di Indonesia: Systematic Review - Annelin Kurniati; Ahmad Fandi; Mardhatillah Sariyanti; Ety Febrianti; Debie Rizqoh (Fakultas Kedokteran, Universitas Andalas, 2021)
Secondary infection with the dengue virus causes mild to severe manifestations. The distribution of dengue virus serotypes varies in various areas and can change over time. There are four dengue serotypes, namely DENV-1, DENV-2, DENV-3 and DENV-4. Objectives: To knew the distribution of virus serotypes in an area and determined the pathogenesis of the disease, which can cause severe manifestations in patients with secondary infections. Methods: The data taken is the severity of secondary infections and dengue serotypes. The literature search was performed on PMC and Cochrane. Search criteria were performed using keywords (secondary infection * OR secondary dengue infection *) AND (Dengue Virus * OR Dengue Infection * OR Dengue * OR DENV) AND (Serotype * OR Serogroup) AND (severe dengue * OR severity * OR severity of illness indexs * OR dengue fever * OR dengue haemorrhage fever * OR dengue shock syndrome * OR DF * OR DHF * OR DSS *) AND (Indonesia *). Results: Literature study search found 387 literature with five studies conducted the analysis. From the results of the analysis, it was found that secondary infections were more common in patients with recurrent dengue infection with serotype 2 (DENV-2), serotype 3 (DENV-3) and serotype 4 (DENV-4). Conclusion: Secondary infection of dengue virus serotype 2 (DENV-2) and serotype 3 (DENV-3) can cause severe dengue infection.Keywords: Dengue Virus, Indonesia, Secondary Infection, Serotype, Severity